New times, new ways: exploring the self-regulation of sport during the COVID-19 pandemic and its relationship with nostalgia and well-being - Cho, Heetae (2023)
Coronavirus disease (COVID-19) has negatively affected individuals' participation in sport activities, while sport participation is an important regulator of well-being. The current study investigated the effects of the nostalgia for sport activities and self-regulation of sport activities on subjective well-being. A total of 302 responses were collected from participants who had engaged in sport activities before the lockdown period. The data were analyzed using partial least squares structural equation modeling (PLS-SEM). The findings showed that nostalgia positively affected the self-regulation of sport and subjective well-being. In addition, self-regulation of sport was positively associated with subjective well-being. Based on the findings of this study, policymakers can implement interventions that promote an individual's feelings of nostalgia, as it might lead them to engage in sport or promote self-regulation.